A transaction cost economics model for estimating performance effectiveness of relational and contractual governance: Theory and statistical results. Issue 11 (7th November 2016) - Wacker, John G.; Yang, Chenlung; Sheu, Chwen
Abstract : Purpose: As outsourcing continues to grow, supplier management becomes critical to the success of manufacturing firms. Transaction cost economics (TCE) suggests that firms should choose supplier governance mechanisms to ensure fulfillment of contractual obligations and safeguard against opportunism for their outsourcing activities. Accordingly, the purpose of this paper is to examine how buying organizations govern supplier contracts to improve manufacturing competitiveness and financial performance. The relative effectiveness of two primary governance mechanisms, contractual governance (CG), and relational governance, are examined. Design/methodology/approach: Expanding upon previous studies, this study delineates three relational governance mechanisms (negotiation efficiency (NE), problem solving relations, and information sharing (IS)) that are conceptually, statistically and pragmatically different. Based on the TCE literature, a conceptual model is developed to decipher the relationships between pre-contract conditions (supplier asset specificity and environmental uncertainty (EU)), governance mechanisms, performance ambiguity (PA), and performance. Using the data collected from 987 firms, the statistical results present several important findings that would advance current theory and practice in outsourcing. Findings: The authors find empirical support for the effects of contractual and relational governance in improving manufacturing and financial performance. The governance of supplier contracts clearly facilitates manufacturers' ability to leverage their resources to improve performance. The relative effectiveness of these two governance mechanisms is related to the levels of EU and supplier asset specificity. Relational governance displays greater influence on performance than CG does. However, CG appears to be complementary to relational governance. Research limitations/implications: The interplays between supplier asset specificity and EU should be examined in the future. The relationships among NE, IS, and problem solving should also be examined to facilitate the development of relational governance. Practical implications: Managers should be aware of the situational performance of governance mechanisms. Moreover, it is important to realize how differently each of the three relational governance mechanisms and CG contribute to performance. Originality/value: This study extends the academic discussion of supplier governance by investigating the alignment of governance mechanisms (relational governance and CG) with pre-contract conditions to reduce PA and, thereby, enhance manufacturing performance. Under the theoretical framework of TCE, the direct and indirect effects of pre-contract conditions and governance variables are fully examined and discussed. Moreover, relational governance involves multiple mechanisms that are conceptually and pragmatically different, and future studies should not treat it as one single construct.